Value of a Simple Method to Assess Chronic Rejection in Renal Allograft on Electron Microscopy. (15th October 2013) - Martínez, Miguel A.; Gil, Yolanda Rodríguez
Abstract: Electron microscopy is a powerful tool for the assessment of complex lesions in nontumor renal pathology, however it is a time-consuming procedure. We evaluated a simple method to assess morphological signs of chronic rejection in renal allograft that seems to have prognostic significance.